The Power of Digital Storytelling: Strengthening Speaking Skills among Secondary EFL Learners - Ulfa Rahma Dhini; Endang Sri Andayani; Syukri Ghozali; Muji Endah Palupi (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study examines the effectiveness of digital storytelling in enhancing the speaking skills of secondary EFL learners. The research responds to persistent challenges in speaking instruction, particularly students’ limited fluency, low confidence, and insufficient exposure to meaningful communicative tasks. Using a mixed methods design, the study involved an eight week intervention in which students created scripted digital stories through narration, multimedia editing, and collaborative production. Quantitative data were collected through pre-test and post-test assessments measuring fluency, pronunciation, vocabulary, and coherence, while qualitative data were obtained through observations, interviews, and student reflections. The findings reveal substantial improvements in speaking performance, especially in fluency and coherence, accompanied by increased engagement, reduced speaking anxiety, and heightened self awareness during the storytelling process. These results highlight that digital storytelling provides repeated oral practice and authentic communicative opportunities that support learners’ linguistic and affective development. The study offers implications for English teachers and curriculum designers by demonstrating that technology supported narrative tasks can be integrated into regular instruction to foster more interactive, creative, and student centered speaking learning environments.